Asymmetrically Fused Nanographene-Porphyrin Architectures - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (European Journal of Organic Chemistry, 2025)
A strategy to combine three standalone aromatic building blocks in one coherent, fully conjugated molecule is presented. Namely, benzene, pyrene, and hexa-peri-hexabenzocoronene (HBC) are assembled around a central porphyrin core in an ABAC type of geometry and interconnected under oxidative Scholl conditions to achieve merging of the individual π-systems. The three asymmetric porphyrin conjugates obtained this way exhibit intriguing absorption features, namely strongly red-shifted and broadened spectra. The presented series of molecules demonstrates the ability to control and influence these optical properties with high precision by altering the size of the aromatic system in a controlled manner. Density functional theory calculations gave more profound insights into the electronic structure and optical transitions of the investigated fused architectures.
CRIS-Team Scopus Importer:2025-01-31
Keywords: fusion reaction; porphyrinoids; post-functionalization; Scholl oxidation; π-extension

A synthetic methodology toward π-extended porphyrin-rylenediimide conjugates - Oleszak, Christoph; Ritterhoff, Christian; Schulze, Erik; Hirsch, Andreas; Meyer, Bernd; Jux, Norbert (RSC Advances, 2025)
In this work, we present a straightforward synthetic route for the preparation of functionalized β-meso-fused porphyrins, which are subsequently connected to rylendiimides. The resulting donor-acceptor-type conjugates exhibit intriguing optical properties, such as panchromatism and profoundly bathochromically shifted absorption curves. A better understanding of the molecules' electronic structure was gained through density-functional theory calculations, which unveiled small HOMO-LUMO gaps.
CRIS-Team Scopus Importer:2025-01-31

Coverage- and temperature-induced self-metalation of tetraphenyltransdibenzoporphyrin on Cu(111) - Shaker, Majid; Muth, Maximilian; Steffen, Julien; Ceccatto Dos Santos, Alisson; Jaekel, Simon; Adhikari, Rajan; Gazetas, Pascal; Oleszak, Christoph; de Siervo, Abner; Jux, Norbert; Görling, Andreas; Lytken, Ole; et al. (Journal of Physics: Condensed Matter, 2025)
We have investigated the adsorption and self-metalation of free-base tetraphenyltransdibenzoporphyrin (2H-TPtdBP) on Cu(111) as a function of coverage and temperature using scanning tunneling microscopy, x-ray photoelectron spectroscopy, temperature programmed desorption, and density-functional theory calculations. At low coverages (<0.16 molecules nm-2), we observe isolated individual molecules with an inverted conformation and no self-metalation up to 363 K. At higher coverages, both the formation of ordered islands and self-metalation are observed over time already at room temperature, and accelerate upon heating to 363 K. At 423 K, complete self-metalation occurs for all coverages up to the completed first layer. By comparing our results for 2H-TPtdBP to the existing literature on other tetraphenyl-based porphyrins, we demonstrate how adsorption and self-metalation can be tailored by the choice of substituents.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DFT; porphyrins; self-assembly; self-metalation; STM; TPD; XPS

Fused Hexabenzocoronene-Porphyrin Conjugates with Tailorable Excited-State Lifetimes - Oleszak, Christoph; Schol, Peter; Ritterhoff, Christian; Krug, Marcel; Martin, Max; Bo, Yifan; Meyer, Bernd; Clark, Timothy; Guldi, Dirk Michael; Jux, Norbert (Angewandte Chemie International Edition, 2024)
A new clear-cut strategy for fusing N-heterocyclic and carbon-pure systems is introduced en route to a versatile platform of multi-purpose tetrapyrrolic chromophores. In particular, three novel C−C bond-fused porphyrin-hexabenzocoronene (HBC) conjugates were synthesized under oxidative cyclodehydrogenation conditions, starting from tailor-made nickel porphyrin precursors. The fusion of the individual aromatic systems via 5-membered rings led to highly soluble π-extended porphyrins in excellent yields. The resulting porphyrin-HBC conjugates exhibit absorption cross-sections that are of interdisciplinary interest in the ever-growing field of organic photovoltaics and near-infrared (NIR) dyes. Quantum chemical calculations show that the newly formed 5-membered rings induce biradicaloid character in the porphyrin core, which has a strong impact on excited state lifetimes. This is confirmed by a thorough optoelectronic and time-resolved characterization in order to understand these unique features better. Broadened absorption characteristics go hand-in-hand with short-lived excited states with up to six orders of magnitude faster decay rates.
CRIS-Team Scopus Importer:2024-10-25
Keywords: biradicaloids; porphyrinoids; post-functionalization; Scholl oxidation; π-extension

Manifold-Fused Porphyrin-Nanographene Conjugates - Oleszak, Christoph; Ritterhoff, Christian; Martin, Max; Meyer, Bernd; Jux, Norbert (Chemistry - A European Journal, 2024)
A library of novel π-extended porphyrin-hexabenzocoronene (HBC) architectures is presented. Two distinct synthetic pathways were utilized to obtain either phenyl- or HBC-fused compounds. Absorption experiments reveal the species’ exciting photophysical and optoelectronic properties. Depending on the degree of π-extension, the number of porphyrins, and their relative position, a decisive change in shape, panchromatic broadening, and red-shifting of the absorption curves is observed. Theoretical studies give more profound insight into the molecule's electronic structures, showing vast decreases in HOMO-LUMO energy gaps.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Fusion reaction; Porphyrinoids; Post-functionalization; Scholl oxidation; π-Extension

Oxidative Cyclodehydrogenation Reactions with Tetraarylporphyrins - Martin, Max; Oleszak, Christoph; Hampel, Frank; Jux, Norbert (European Journal of Organic Chemistry, 2020)
The extension of the aromatic π-system of porphyrins is a powerful method to alter their optoelectronic properties. Herein, aryl substituents were fused to porphyrin cores by Scholl oxidation reactions that selectively produced mono- and doubly-fused porphyrins in yields of up to 69 %. Several different aryl substituents attached to the porphyrin were investigated with respect to their reactivity under Scholl conditions. The fused products were fully characterized, i.e., by UV/Vis absorption spectroscopy, which showed drastic changes in the electronic features. Insight into the solid-state behavior was obtained by X-ray crystallography. Our approach represents a novel option for the late-stage functionalization of porphyrin-based compounds.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Fusion reaction; Porphyrinoids; Post-functionalization; Scholl oxidation; π-Extension

Panchromatic PAH-Porphyrin Hybrids with a Step-Wise Increasing π-System - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (ChemistryOpen, 2025)
The rational synthesis of three β-meso-fused porphyrins with a step-wise increasing π-system size is presented. The synthetic route, which introduces a five-membered ring between the macrocycle and an aromatic fragment, is modular in its nature and proceeds straightforwardly. The well-soluble conjugates have intriguing optical properties, namely bathochromically shifted and flattened absorption curves. Density functional theory (DFT) calculations provide insights into the electronic structure and transitions, unveiling small HOMO-LUMO gaps.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Fusion reaction; Porphyrinoids; Post-functionalization; Scholl oxidation; π-extension

Supramolecular complexation of C60 and C70 by helical nanographene incorporating N-heterotriangulene and hexabenzocoronene subunits - Kinzelmann, Marina; Fröhlich, Nina; Gnannt, Frederik; Borstelmann, Jan; Frühwald, Stefan; Oleszak, Christoph; Jux, Norbert; Görling, Andreas; Kivala, Milan; Drewello, Thomas (RSC Advances, 2025)
Supramolecular host–guest complexes are studied in the gas-phase evaluating a new host molecule for fullerenes (C60 and C70). The new host molecule is a double N-heterotriangulene-[5]helicene (NTH), consisting of two N-heterotriangulene (N-HTA) blades embedded into a hexabenzocoronene-like backbone with helically curved topology. Host–guest complexes of [1:1]+c/2+, [1:2]+c/2+, [2:1]2+ and [2:3]2+ stoichiometry and charge state are formed by electrospray ionization-mass spectrometry (ESI-MS). Ion formation occurs through electrochemical oxidation of the N-HTA moieties. Energy-resolved collision-induced dissociation (ER-CID) experiments reveal the noncovalent binding of the fullerenes to the NTH molecule and provide an order of stability for the complexes. Density-functional theory (DFT) calculations establish the lowest energy geometries of the complexes.
CRIS-Team Scopus Importer:2025-02-14

β-meso-Fused pyrene–porphyrin scaffolds with panchromatic absorption features - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (Organic & Biomolecular Chemistry, 2024)
The π-extension of porphyrins with pyrenes through the β-mesofusion of five-membered rings is demonstrated. Three architectures resulting from combining up to two porphyrins and pyrenes were obtained straightforwardly in good overall yields. Although significantly planarized, the molecules retain excellent solubility and processability. Spectroscopic characterization and density-functional theory calculations reveal intriguing absorption features.
CRIS-Team Scopus Importer:2025-02-04